A revision of the 13C NMR spectral assignment of globulol. Issue 2 (1999) - Toyota Toyota, Masao Masao; Tanaka Tanaka, Masami Masami; Asakawa Asakawa, Yoshinori Yoshinori
Abstract : Complete assignment of the 13 C NMR spectrum of the aromadendrane‒type sesquiterpene alcohol, globulol was reported, however, it still remained to be ambiguous. We report here the unambiguous and complete assignment of the 1 >H and 13 C NMR spectra of (+)‒globulol, which was isolated from the liverworts Plagiochila ovalifolia, Neotrichocolea bissetii and Pallavicinia subciliata